Adsorption Properties of Activated Tire Pyrolysis Chars for Phenol and Chlorophenols. Issue 4 (10th March 2020) - Kuśmierek, Krzysztof; Świątkowski, Andrzej; Kotkowski, Tomasz; Cherbański, Robert; Molga, Eugeniusz
Abstract: The adsorption of phenol (Ph), 4‐chlorophenol (4CP), and 2, 4‐dichlorophenol (DCP) from aqueous solutions on activated tire pyrolysis chars (ATPCs) was studied in a batch system, including both kinetics and equilibrium. Different kinetic models and adsorption isotherms were used to describe the adsorption behavior of the phenols. The kinetic study shows that the process can be described by a pseudo‐second‐order model. The best fitting results for the equilibrium adsorption data were obtained with the Sips isotherm. Adsorption of the selected phenols on all of the adsorbents increased in the order Ph < 4CP < DCP. The effect of ionic strength and pH on the adsorption was also studied. The results show that the ATPCs could be used as adsorbents for the removal of phenols from aqueous solutions. Abstract : Pyrolysis has experienced a renaissance in recent years. It has also become a more frequently used method for end‐of‐life tire processing. Nowadays, the pyrolysis products are valorized to improve process sustainability. This work demonstrates upgrading tire pyrolysis char for efficient adsorption of phenol and its chlorinated derivatives from aqueous solutions.